PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI MELALUI MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) DENGAN MENGGUNAKAN MEDIA CERITA BERGAMBAR - Dina Siti Patimah Dewi; Teti Sobari; Riana Dwi Lestari (IKIP Siliwangi, 2026)
Based on the results of interviews with teachers in the field of Indonesian studies at SMP Plus Sindang Resmi (SMP Plus Sindang Resmi), the student's narrative text writing activity has not shown satisfactory results. Students have difficulty in pouring ideas on the theme that has been given. This is evidenced by the results of daily tests carried out. This study aims to determine the increase in student activities and the effectiveness of the application of the CORE model by using pictorial story media in learning to write narrative texts for junior high school students in grade VII. The method used is a mix method with a sequential exploratory design model. The data collection technique uses qualitative techniques in the form of observation and quantitative data is collected in the form of tests (pretestt and posttest). The subjects in the study were grade VII students of SMP Plus Sindang Resmi with a total of 31 students. The results of the study showed an increase in the score, which was initially an average score of 67.80 in the pretest, after applying the CORE learning model with the help of illustrated story media, the average score of students in the posttest increased to 78.58. Based on the results of the N-Gain test, a value of 0.36 with a vulnerability of 0.3 ≤ g ≤ 0.7 can be categorized as